210k views
5 votes
Factor completely. 36c^2−8cd+49d^2

User Kumar Kush
by
5.4k points

2 Answers

5 votes

Answer:

(6c-7d)^2

Explanation:

khan

User Antuan
by
4.7k points
7 votes


\huge\bold\green{Answer:-}

Simplifying

36c2 + -84cd + 49d2 = 0

Reorder the terms:

-84cd + 36c2 + 49d2 = 0

Solving

-84cd + 36c2 + 49d2 = 0

Solving for variable 'c'.

Factor a trinomial.

(6c + -7d)(6c + -7d) = 0

Subproblem 1

Set the factor '(6c + -7d)' equal to zero and attempt to solve:

Simplifying

6c + -7d = 0

Solving

6c + -7d = 0

Move all terms containing c to the left, all other terms to the right.

Add '7d' to each side of the equation.

6c + -7d + 7d = 0 + 7d

Combine like terms: -7d + 7d = 0

6c + 0 = 0 + 7d

6c = 0 + 7d

Remove the zero:

6c = 7d

Divide each side by '6'.

c = 1.166666667d

Simplifying

c = 1.166666667d

Subproblem 2

Set the factor '(6c + -7d)' equal to zero and attempt to solve:

Simplifying

6c + -7d = 0

Solving

6c + -7d = 0

Move all terms containing c to the left, all other terms to the right.

Add '7d' to each side of the equation.

6c + -7d + 7d = 0 + 7d

Combine like terms: -7d + 7d = 0

6c + 0 = 0 + 7d

6c = 0 + 7d

Remove the zero:

6c = 7d

Divide each side by '6'.

c = 1.166666667d

Simplifying

c = 1.166666667d

Solution

c = {1.166666667d, 1.166666667d}

I HOPE IT HELPS ♥️

User Bruno Laurinec
by
4.9k points